Putting Inequality in Context : Class, Public Opinion, and Representation in the United States - Ellis, Christopher, 1978- (Book collections on Project MUSE., 2017)
Rising income inequality is highlighted as one of the largest challenges facing the United States, affecting civic participation and political representation. Although the wealthy often can and do exert more political influence, this is not always the case. To fix political inequality, it is important to understand exactly how class divisions manifest themselves in political outcomes, and what factors serve to enhance, or depress, inequalities in political voice.